Dystocia due to Fetal Hydrocephalus in a Non-Descript Nulliparous Doe - Shivamurthy, Bhargav; Sengodan, Raja; Gopikrishnan, Duraisamy; Palanisamy, Mahakrishnan; Selvaraju, Mani; Murugan , Manickam (The Indian Journal of Animal Reproduction, 2025)
A one-year-old nulliparous non-descript doe was presented with the history of delivery of a live kid 24 hours before and straining with no progress. Vaginal examination revealed fully dilated cervix with the foetus in anterior longitudinal pre sentation, dorso sacral position with bilateral shoulder flexion and enlarged fetal head suggesting hydrocephalus. Under epidural anaesthesia, a dead female fetus was relieved by mutation and controlled traction and the doe was treated with an antibiotic, antihistaminic, anti-inflammatories and an ecbolic for three days resulting in uneventful recovery.